Cover Image, Volume 138, Issue 2. Issue 2 (28th September 2020) - Mandal, Subhash; Roy, Debmalya; Prasad, Namburi Eswara; Joshi, Mangala
Abstract : Periodic phase segregated geometries have been reported in bulk state for thermoplastic polyurethanes. The thermo‐responsive supramolecular self‐assembly critically influences the fundamental ordering units and causes shifting in phase boundaries of physiochemically dissimilar blocks of segmented polyurethanes. The cover image designed by Subhash Mandal and colleages shows the role of how low dimensional nanofillers were highlighted to control the transformational kinetics of homogeneous one‐phase system at higher temperature to the two‐phase quasi‐equilibrium state at room temperature. The topologically controlled folded lamellar morphologies in the soft and hard blocks of segmented polyurethane chains, as shown in the figure, were generated by using the highly porous 3D hierarchical hybrid carbonaceous nanoscale building blocks. DOI: 10.1002/app.49775